Global Maritime Fulcrum Optimization In Maintaining Indonesian Maritime Sovereignty - Muhammad Sholeh, Nur Rohim Yunus, Ida Susilowati (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
The regulation of International maritime law has become a long-standing discussion in International life. It is not surprising if many international conventions were born as a result of agreements between countries. The main trigger for the occurrence of sea conflicts is the potential for extraordinary marine wealth that can be exploited by the International community. Therefore, the regulation of sea law is vital in order to maintain discipline and world peace and in addition to protecting the sovereignty of each country. This research uses a qualitative research method with a descriptive analysis approach.